A Solution‐Processed UV‐Sensitive Photodiode Produced Using a New Silicon Nanocrystal Ink. (25th July 2014) - Lin, Tao; Liu, Xin; Zhou, Bin; Zhan, Zhiyong; Cartwright, Alexander N.; Swihart, Mark T.
<x xml:space="preserve">Abstract</x> This article presents a simple and effective method of functionalizing hydrogen‐terminated silicon (Si) nanocrystals (NCs) to form a high‐quality colloidal Si NC ink with short ligands that allow charge transport in nanocrystal solid films. Si NCs fabricated by laser‐pyrolysis and acid etching are passivated with allyl disulfide via ultraviolet (UV)‐initiated hydrosilylation to form a stable colloidal Si NC ink. Then a Si NC‐based photodiode is directly fabricated in air from this ink. Only a solution‐processed poly(3, 4‐ethylenedioxy‐thiophene):poly(styrene sulfonate) (PEDOT: PSS) electron blocking layer and top‐ and bottom‐contacts are needed along with the Si NC layer to construct the device. A Schottky‐junction at the interface between the Si NC absorber layer and aluminum (Al) back electrode drives charge separation in the device under illumination. The unpackaged Si NC‐based photodiode exhibites a peak photoresponse of 0.02 A W−1 to UV light in air, within an order of magnitude of the response of commercially available gallium phosphide (GaP), gallium nitride (GaN), and silicon carbide (SiC) based photodetectors. This provides a new pathway to large‐area, low‐cost solution‐processed UV photodetectors on flexible substrates and demonstrates the potential of this new silicon nanocrystal ink for broader applications in solution‐processed optoelectronics.